Structure of acute intestinal infections in the Arkhangelsk region from 2020 to 2022. A clinical case of a mixed form of acute intestinal infection - М. A. Pozdeeva; Yu. S. Tsvetkova; M. A. Kashunina (Лечащий Врач, 2024)
Background. Currently, acute intestinal infections are still one of the key health problems both around the world and in Russia. In addition to the obvious health hazards that arise, which are predominantly prevalent among children, these diseases are also an economic problem.Objective. Analyze the composition of pathogens of acute intestinal diseases in the Arkhangelsk region on the basis of official statistical information and data provided by Primorsky Central District Hospital of Arkhangelsk.Materials and methods. The method of analyzing data from current literature sources and the provided polyclinic database was used.Results. Acute intestinal infections are a broad group of diseases, polyetilogical and extremely diverse in their composition, epidemiology and clinical manifestations. One of the key classifications is the division of pathogens into bacterial and viral. At the moment, it is noted that among bacteria the main pathogens are salmonella and shigella. Among viral acute infections, rotaviruses and noroviruses are recognized as the leading etiological agents. According to statistical data, in the Arkhangelsk region there is a tendency to increase the incidence of acute intestinal infections among the entire population: in 2020, 4496 cases were registered, in 2021 and 2022 – 4347 and 5315 cases, respectively. It is cases with an unknown etiology that are rapidly increasing and prevail among all morbidity. In situations where the pathogen is known, the diseases most often recorded in the Arkhangelsk region were salmonellosis (351 cases in 2020, 186 cases in 2021, 190 cases in 2022), shigellosis (10 cases in 2020, 3 and 1 case in 2021 and 2022, respectively), rotavirus (in 2020 65% of the entire structure, in 2021 – 78.8%, in 2022 – 73.5%) and noravirus infection (in 2020 20.9% of cases, in 2021 – 13.6%, in 2022 – 19.1%). The average age of a patient with ACI is 36 years, children make up 9% of the total incidence.Conclusion. Unfortunately, the diagnosis of pathogens of acute intestinal infections is at a fairly low level, so most often the etiology remains unknown. In cases where the pathogen can be identified, Salmonella spp. dominates among the bacteria that cause this group of diseases, rotaviruses and noroviruses dominate among viruses, and a mixed infection is increasingly observed, requiring carefully selected therapy.